Design and development of controller of a rotary crane system - Ali Azhar, F.E.; Rashid, Muhammad Mahbubur; Alamgir, Tarik Bin (2012)
The rotary cranes (tower crane) main purpose in finding a proper control strategy to transport the loads from one location to another. The controlling approach should consider two main factors which are minimizing the moving time of the payload from the primary pick up point to the destination point and second, the oscillation of the payload must be reduced to prevent hazards for people and equipment in the workplace. These days, instead of skillful crane operator, a lot of controllers have designed for the purpose of minimizing angle of swing as well as obtaining precise positioning. However, still each of them has some limitations and an enhanced controller is necessary with the aim of increasing the efficiency of the rotary crane system. In this research, input shaping technique, a technique of convolving the impulse sequences, an input shaper, with the command signal of the system is implemented into the rotary crane system. The outcome of the convolution is then being used as the reference command to drive the system. The inputs for the system are the position and the angle of swing that are being detected by the encoder and potentiometer. These inputs are converted into digital signal by the means of DAQ card. Then, after they are being manipulated with the design input shaper in the MATLAB simulation software, the simulation model will then be connected to the real system by using the XPC Target. The execution of the MATLAB simulation on the target PC will result in reduced angle of swing of the rotary crane system. This project is very significant due to fact that it brings an improvement in controlling the angle of swing of the rotary crane and minimizes the time needed to move the payload.